Electroanalytical determination of bumetanide employing a biomimetic sensor for detection of doping in sports - Santos Ruy, Mayara Regina dos [UNESP]; Figueira, Eduardo Carneiro [UNESP]; Taboada Sotomayor, Maria Del Pilar [UNESP] (Royal Soc Chemistry, 2014)
This paper describes the development and application of a simple, cheap, and clean method for the quantification of bumetanide in urine samples from athletes and in pharmaceutical formulations to detect doping, using a biomimetic sensor based on a carbon paste modified with copper(II) 1,2,3,4,8,9,10,11,15,16,17,18,22,23,24,25-hexadecafluoro-29H,31H-phthalocyanine (a biomimetic catalyst of the P450 enzyme). The sensor was evaluated using cyclic voltammetry and square wave voltammetry, for electrochemical characterization and quantification purposes, respectively. Square wave voltammetry analyses were carried out vs. Ag/AgCl (KClsat), using a 0.15 mol L-1 Britton-Robinson buffer solution at pH 7.0 as the support electrolyte. This method was optimized using a chemometric experimental design. Under these optimized analytical conditions, the sensor showed a linear response between 9.9 x 10(-7) and 8.3 x 10(-6) mol L-1 (R = 0.996) and limits of detection and quantification of 2.7 x 10(-7) and 9.0 x 10(-7) mol L-1, respectively. The proposed method was successfully applied in the analysis of bumetanide in spiked urine, demonstrating that it is a reliable alternative method for the detection of bumetanide doping in sport.